2010
DOI: 10.1002/ijc.25193
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor 1 expression correlates with clinical outcome in K‐RAS wild type colorectal cancer patients treated with cetuximab and irinotecan

Abstract: Seventy to 40% of K-RAS wild type colorectal tumors does not seem to benefit from treatment with antiepidermal growth factor receptor (anti-EGFR) monoclonal antibodies. Recent data suggested that in presence of IGF-1 system, altered activation colorectal cancer cells may escape anti-EGFR mediated cell death. The interaction between IGF-1 expression and K-RAS mutational analysis was tested to verify the ability of IGF-1 to identify a subgroup of patients more likely to benefit from EGFR-targeted antibodies trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 30 publications
0
56
0
2
Order By: Relevance
“…This notion was further supported by the finding that the level of serum HGF relates to the efficacy of this treatment modality in patients with KRAS wild-type disease (23). In addition to HGF, overexpression of insulin-like growth factor I produced by cancer cells itself has been suggested to mediate resistance to cetuximab (24). Intriguingly, besides stimulation of parallel RTK pathways by ligands, also amplifications and upregulation of alternative RTKs convey resistance to anti-EGFR therapy as the case of HER2 shows (25).…”
Section: Colorectal Cancer Heterogeneity and Predictors Of Responsementioning
confidence: 89%
“…This notion was further supported by the finding that the level of serum HGF relates to the efficacy of this treatment modality in patients with KRAS wild-type disease (23). In addition to HGF, overexpression of insulin-like growth factor I produced by cancer cells itself has been suggested to mediate resistance to cetuximab (24). Intriguingly, besides stimulation of parallel RTK pathways by ligands, also amplifications and upregulation of alternative RTKs convey resistance to anti-EGFR therapy as the case of HER2 shows (25).…”
Section: Colorectal Cancer Heterogeneity and Predictors Of Responsementioning
confidence: 89%
“…Interestingly, and consistently with the hypothesis of ADCC as an important mechanism of action of cetuximab against micrometastases, we found that carriers of 131R and/or 158F alleles had a significantly lower risk of distant failure than patients homozygous for 131H and/or 158V when cetuximab was added to the study sequential treatment. It is worth noting that additional signaling pathways beyond EGFR (i.e., IGF-1R pathway) which have been shown to cross-talk with EGFR downstream effectors and mediate the ADCC-independent therapeutic effects of cetuximab are more frequently activated and potentially more clinically relevant in rectal cancer than in colon cancer (36)(37)(38). Therefore, our findings could be potentially influenced by the specific location of the primary tumor and may not apply to a population of patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al reported that the combination of both K-ras and IGFR1 antisense oligodeoxynucleotide cooperatively inhibited the growth of pancreatic cancer cell lines in vitro, and induced their apoptosis in vivo (22). Furthermore, combined IGF-1 and K-ras analyses have been shown to be beneficial for the better selection of colorectal cancer patients that may respond to therapy (23). Therefore, a new strategy to co-target both IGFR-1 and K-ras may be required to control lung cancers expressing IGFR1 with the K-ras mutation.…”
Section: Discussionmentioning
confidence: 99%